2018
DOI: 10.29252/jafm.11.05.28588
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and CFD Study of Internal Flow inside a Sessile Microdroplet undergoing Lateral Vibration

et al.

Abstract: In this study, the internal flow pattern of a sessile microdroplet undergoing a lateral vibration was analyzed by using both the experimental and CFD simulation methods. By initially staining the droplet partially with fluorescent dye, the main flow inside the laterally vibrating microdrop was experimentally demonstrated to be that the main fluid flows downward along the central axis and ascends upward along the surface to form two counterflow circuits. Experimental evaluation of fluid mixing inside the drople… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…T-junction microchannels are widely used in the process of producing droplets, and the internal circulation flow within the droplets can be induced universally by shear stress between two phases. The droplet internal flow details in T-junction microchannels have been investigated by applying microparticle image velocimetry (μPIV) experiments and CFD analysis. Using μPIV, Kinoshita et al obtained the three-dimensional flow structure inside the droplet, which indicated different circulation topologies in planes at four different depths . These studies helped us to understand the circulation inside droplets, whereas most of them only focused on the circulation flow on certain horizontal or vertical planes.…”
Section: Introductionmentioning
confidence: 99%
“…T-junction microchannels are widely used in the process of producing droplets, and the internal circulation flow within the droplets can be induced universally by shear stress between two phases. The droplet internal flow details in T-junction microchannels have been investigated by applying microparticle image velocimetry (μPIV) experiments and CFD analysis. Using μPIV, Kinoshita et al obtained the three-dimensional flow structure inside the droplet, which indicated different circulation topologies in planes at four different depths . These studies helped us to understand the circulation inside droplets, whereas most of them only focused on the circulation flow on certain horizontal or vertical planes.…”
Section: Introductionmentioning
confidence: 99%
“…Rotating disk electrodes (RDE) can be utilized in which a single droplet is confined between a rotating disk and a fixed substrate 40,41 . A droplet-carrying substrate can be driven into vertical or horizontal oscillation causing flows when the droplet vibrates at one of its resonant states 13,[42][43][44] . The above methods have limitations in their applications, however.…”
Section: Introductionmentioning
confidence: 99%
“…In such practical applications, the flow field developed within and around the sonically excited droplets remains critical for droplet mobility over the surfaces. Since the precise experimental investigation for internal fluidity and external flow around the excited droplets is extremely challenging, the numerical predictions of the flow field remain fruitful 20 . Nevertheless, accurate flow predictions can shed light on the droplet behavior over the vibrating surfaces and provides useful guidance for experimental investigations.…”
Section: Introductionmentioning
confidence: 99%